Spatial and temporal variation of anthropogenic black carbon emissions in China for the period 1980–2009 - Qin, Y.; Xie, S. D. (Atmospheric Chemistry and Physics, 2012)
Multi-year inventories of anthropogenic black carbon emissions, including both fuel consumption and biomass open burning, at a high spatial resolution of 0.25°×0.25° have been constructed in China using GIS methodology for the period 1980–2009, based on official statistical data and time-varying emission factors. Results show that black carbon emissions increased from 0.87 Tg in 1980 to 1.88 Tg in 2009 with a peak in about 1995, and had been continually increasing in the first decade of the 21 century. Residential contribution to the total BC emissions declined from 82.03% in 1980 to 42.33% in 2009 at a continuous diminishing trend, but had always been the dominant contributor in China. While contributions from industry and transportation sectors had increased notably. BC emissions were mainly concentrated in the central eastern districts, the three northeastern provinces and the Sichuan Basin, covering 22.30% of China's territory, but were responsible for 43.02%, 50.47%, 50.69% and 54.30% of the national black carbon emissions in 1985, 1995, 2005 and 2009, respectively. Besides, China made up 70%–85% of BC emissions in East Asia, half of the emissions in Asia, and accounted for averagely 18.97% of the global BC emissions during the estimation period.